A cultura informacional como alicerce de gestão contábil nas pequenas e médias empresas - Smith, Marinês Santana Justo [UNESP] (2013)
Small and medium enterprises (SME) play a major role in the national economy, yet they are vulnerable to diversities imposed on the business environment, requiring new positions in managing their resources, which also infers information management. The study highlights the accounting information which demonstrates the economic and financial situation of the business. The research begins with the assumption that the organizational culture determines the information culture which impacts choices in the generation of accounting information with focuses on the resulting financial management. Thus one can treat the perception of the mandatory SPED - Public Digital Bookkeeping System – as an opportunity to extract management information from the otherwise unused or only rarely used and turn it into a management tool. However it can also reveal that the value of accounting information is only to meet legal requirements. Aiming to leverage the accounting information as a value to be incorporated in the financial management of SME, it aims to contribute to the construction of a conceptual model of accounting information management that has as its foundation the organizational and informational culture that supports the generation of information assets from the detailed information required by SPED. And based on this model, the influence of information culture in the shoe manufacturing companies of Franca was analyzed regarding accounting information management for managerial use. For this, a theoretical discussion of information, information and knowledge management, informational assets, legal requirements, corporate and management accounting, organizational and informational culture was presented. This discussion allowed the construction of the proposed model Accounting Information Management under Information Culture Perspective (GICPCI)... (Complete abstract click electronic access below)